Correlation between Self-Efficacy on Diabetes Self-Management in Middle Age with Type 2 Diabetes Mellitus - Dwitanta, Sucipto (Universitas Muhammadiyah Tangerang, 2024)
Middle-aged patients with diabetes have a higher risk of comorbidities, and the risk of more severe disease is associated with poor glycemic control behavior. Diabetes self management is essential to control blood sugar. Success of the diabetes self-management is influenced by several factors, one of which is self-efficacy. Purpose of this study was to determine whether there is a relationship between self-efficacy towards diabetes self-management in middle age with Type 2 Diabetes Mellitus. Method in this study used a cross-sectional design approach. Sampling used the consecutive sampling method according to the inclusion and exclusion criteria. The number of samples is 91 respondents. The results of the study found female gender (63.7%), 5-10 years of illness (69.2%) and low economic status (1.1%). Statistical results showed that there was a significant relationship between self-efficacy and diabetes self-management (p=0.000). Self-efficacy abilities are needed in patients with type 2 DM in self-care activities. Self-efficacy is fundamental because self-efficacy is something that is already within the individual, the emergence of self-efficacy will be caused by the emergence of strong motivation and ability that emerges in the form of an individual's attitude. With strong self-efficacy, you will have a self-care attitude.